The Prevalence and Intensity of Louse (Pthiraptera, Mallophaga) and Tick (Acarina,Ixodidae) Infestation of Birds in South African Grassland - Kopij, G.; Price, R.D. (Вестник зоологии, 2011)
A total of 270 birds represented by 12 species were examined for the presence of lice and ticks. Birds were collected in South African grasslands. Extensity of louse and tick infestation ranged from 10% to 80% and from 3% to 33% respectively. Average number of lice per host species ranged from 1 to 15, while average number of ticks per host species ranged from 1 to 5. Only single specimens (0.4%) were heavily parasited by lice and ticks respectively. Lice infested birds more often during the dry season, while ticks infested birds mainly during the rain season.